The Effectiveness of Injection of Trigger Points with Platelet Rich Plasma as A Pain Management Method in Chronic Tension Type Headache - Algawwam, Hayder Ghali; Mohammad, Abdullah Ahmed (Journal of medical and pharmaceutical sciences, 2019)
Objective: This study designed to evaluate the effectiveness of injection of trigger points with platelet rich plasma as a pain management method in chronic tension type headache. Methodology: a retrospective study conducted over 2.5 year period (July 1, 2016- March 31, 2018), 71 patients (57 females and 14 males) in Dr Abdullah Al-Karboli Medical Center For Family Medicine And Pain Management in Kirkuk, Iraq because of CTTH, they received trigger points PRP injections. The PRP was prepared by centrifuging patients’ own blood. The response to therapy was graded as excellent, good, fair and poor. Results: The mean age was 48.1± 1.5 years. Most of patients (n: 52, 73.2%) yielded either good or excellent response to treatment, while (n: 19, 26.8%) from patient had either fair or poor response to treatment, there was statistically significant difference between the 2 groups. Conclusion: Trigger points injection with PRP seems to be an effective, safe and cheap pain management method in CTTH.